2007
DOI: 10.1080/00131910701619290
|View full text |Cite
|
Sign up to set email alerts
|

Learning Cultures in Further Education

Abstract: This paper examines the nature of learning cultures in English Further Education (FE), as revealed in the Transforming Learning Cultures in FE (TLC) research project. In it, we describe four characteristics of a generic FE learning culture: the significance of learning cultures in every site; the significance of the tutor in influencing site learning cultures; the often negative impact of policy and management approaches; and the ever-present issue of course status. We go on to different types of learning cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 11 publications
(15 reference statements)
1
25
0
Order By: Relevance
“…Our thinking does not invalidate the latter, but allows teacher inputs to be seen as but one part of a complex cultural whole. Our research in English Further Education also suggested that learning is more likely to be effective if many of the forces that interact in the field of a learning culture are acting broadly in synergy, and that learning is less likely to be effective where the learning culture is marked by dysfunctional conflicts and tensions (Hodkinson et al 2007). Thus, where the concern is with promoting effective learning, changing the learning culture, including its social and institutional dimensions, in ways likely to increase synergy could be very profitable, but this is an almost completely neglected approach.…”
Section: Different and Better Questionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our thinking does not invalidate the latter, but allows teacher inputs to be seen as but one part of a complex cultural whole. Our research in English Further Education also suggested that learning is more likely to be effective if many of the forces that interact in the field of a learning culture are acting broadly in synergy, and that learning is less likely to be effective where the learning culture is marked by dysfunctional conflicts and tensions (Hodkinson et al 2007). Thus, where the concern is with promoting effective learning, changing the learning culture, including its social and institutional dimensions, in ways likely to increase synergy could be very profitable, but this is an almost completely neglected approach.…”
Section: Different and Better Questionsmentioning
confidence: 99%
“…Rather, each factor was influenced by the others, and it was the relations between them that influenced learning. One result was that practices and understandings of learning proved to be very different from one site to another, for the relations between these influences differed significantly between them (see Hodkinson et al 2007, for a fuller discussion of this issue, together with an identification of some common cultural influences across English Further Education as a whole). Here, we do not have space to present the evidence from that study which underpins many of out arguments.…”
mentioning
confidence: 99%
“…(e.g. Hodkinson 2005aHodkinson , 2005bHodkinson et al 2007). Narrow definitions of quality, set within targets and Performance Indicators (PIs) by Ofsted and LSC, it is argued, had continued to restrict lecturers' performance and effectiveness, and the one-size-fits-all view of what works, allied to measures of retention and achievement, had been inadequate for improving teaching and learning.…”
Section: Introductionmentioning
confidence: 99%
“…Hodkinson, 2005b, Hodkinson et al, 2007 suggests that current Coalition policy (as with New Labour's before it) is unlikely to succeed at improving student learning because learning is a social process rather than something which can be mandated from above. To improve teaching and learning, it is argued, will require lecturer autonomy and opportunities for professional development rather than topdown policy premised on the assumption of agent self-interest.…”
Section: Network In the Fe Sectormentioning
confidence: 99%
“…Hodkinson, 2005a, 2005b, Hodkinson et al, 2007. The audit culture created by Ofsted and LSC, focused on quantitative measures of success, and sustained by managerialist approaches, was accused of undermining the morale of lecturers because of the constant need to defend the existing 'learning culture' against change (in the shape of reorganisations, mergers and funding) driven by the need to improve performance indicators for survival within the FE quasi-market.…”
Section: The Impact Of the Balance Of Rational Goals And Self-governamentioning
confidence: 99%